Current and future prospects for heat recovery from waste in European district heating systems: A literature and data review. (1st September 2016) - Persson, Urban; Münster, Marie
Abstract: Municipal solid waste has seen increasing annual volumes for many decades in contemporary Europe and constitutes, if not properly managed, an environmental problem due to local pollution and greenhouse gas emissions. From an energy perspective, waste is also an alternative fuel for power and heat generation; energy recovery from waste represents an effective measure to reduce landfilling and avoid disposal emissions while simultaneously reducing the equivalent demand for primary energy supply. A key factor for obtaining the full synergetic benefits of this energy recovery is the presence of local heat distribution infrastructures, without which no large-scale recovery and utilisation of excess heat is possible. In this paper, which aims to estimate municipal solid waste volumes available for heat recovery in European district heating systems in 2030, a literature and data review is performed to establish and assess current and future EU (European Union) waste generation and management. Main conclusions are that more heat can be recovered from current Waste-to-Energy facilities operating at low average heat recovery efficiencies, that efficient incineration capacity is geographically concentrated, and that waste available for heat recovery in 2030 is equally determined by total generation volumes by this year as by future EU deployment levels of district heating. Highlights: European municipal solid waste time series data analysed from 1995 to 2012. Review of modelling approaches to assess future European waste generation. Weather corrected district heat data for EU Member States in 1995 and 2012. Low average heat recovery efficiency in current European waste incineration. Future heat recovery efficiencies as determinant as future generation volumes.